Second Men in Shakespeare's Tragedies - Málek, Ondřej (Univerzita Pardubice, 2013)
This bachelor thesis focuses on the 'second men' in selected works of William Shakespeare's tragedies and aims to show their importance in the story. The analysis of the 'second men' is conducted on the basis of the findings from the archetypal and formalist criticism with the special emphasis on the functions they fulfill, on their roles in nemesis and on their position in the demonic world. On the basis of these findings, archetypes of these characters can be found.
Druzí muži v Shakespearových tragédiích
Keywords: function; characters; nemesis; archetypes; funkce; postavy; nemesis; archetypy